2019
DOI: 10.1002/jwmg.21666
|View full text |Cite
|
Sign up to set email alerts
|

Land use and dispersal influence mortality in white‐tailed deer

Abstract: Restoring male age structure in white‐tailed deer populations has become an important objective for many state agencies aimed at improving herd dynamics. Limiting mortality in the yearling (1–2 yr old) age class is a primary consideration, and regional differences in climate, habitat characteristics, hunting regulations, and hunter behavior complicate the understanding of how specific factors influence the risk of mortality. We used Cox proportional hazard modeling to determine the effects of body size, mean d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 97 publications
4
23
4
Order By: Relevance
“…In each case, the null model (circles) was more parsimonious than models that estimated survival of dispersers (triangles) and nondispersers (squares) separately Trewhella, 1988;Johnson et al, 2009;Jones, 1988). Although we did not detect a significant effect of dispersal distance on survival, Haus et al (2019) found decreased mortality with increasing dispersal distance in yearling male white-tailed deer. As in our study system, hunting was the largest source of mortality, and vehicular collision was relatively minor, although they did not specify if any of the observed vehicular collisions occurred during transfer.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In each case, the null model (circles) was more parsimonious than models that estimated survival of dispersers (triangles) and nondispersers (squares) separately Trewhella, 1988;Johnson et al, 2009;Jones, 1988). Although we did not detect a significant effect of dispersal distance on survival, Haus et al (2019) found decreased mortality with increasing dispersal distance in yearling male white-tailed deer. As in our study system, hunting was the largest source of mortality, and vehicular collision was relatively minor, although they did not specify if any of the observed vehicular collisions occurred during transfer.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with this, male dispersal movements in our study were quick (often <12 hr), direct, and relatively short (median dispersal distance in our system = 5.9 km; Long, 2005;Long et al, 2010), although dispersal movements in more agricultural landscapes are often longer in duration and distance (Anderson et al, 2015;Springer, 2017). These findings suggest that males have adapted efficient dispersal strategies, and like our study, Haus et al (2019) found no effect of dispersal on yearling male white-tailed deer survival in Delaware, USA.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We used package survival in Program R for survival analysis (Therneau 2015). We used a study‐based time period (1 May [0]–30 Apr [364]) for all years (Fieberg and DelGiudice 2009, Haus et al 2019). We used the Kaplan‐Meier estimator (Kaplan and Meier 1958) to calculate a baseline annual survival curve with the Greenwood variance estimator to generate 95% confidence intervals.…”
Section: Methodsmentioning
confidence: 99%